The robust catalysts (Ni1−x–Mox/doped ceria and Zn1−x–Mox/doped ceria, x = 0.1 and 0.3) for efficient natural gas reforming in solid oxide fuel cells. (20th November 2020) - Naseer, Amtul; Hussain, Murid; Shakir, Imran; Abbas, Qaisar; Yilmaz, Duygu; Zahra, Marriam; Raza, Rizwan
Highlights: Doping of Mo in Ni–GDC and Zn–GDC anodes for natural gas based SOFC. Ni–Mo–GDC exhibits maximum power density of 690 mW cm −2 at 600 °C. The addition of Mo in Ni–GDC and Zn–GDC anodes improves carbon deposition. Abstract: Nickel is a promising catalyst in Solid Oxide fuel cell (SOFC) due to its electrocatalytic performance, however, the practical utilization of Ni-based materials is hindered by the undesirable carbon deposition during methane decomposition. Herein, molybdenum is incorporated into the Ni- and Zn-based cermets (Ni1 − x –Mo x /GDC and Zn1 − x –Mo x /GDC, x  = 0.1 and 0.3) to enhance electrocatalytic properties and avoid the carbon deposition during cell operation. The desired composites are synthesized by the impregnation method and adopted as anode in SOFCs. The catalytic activity for methane oxidation has been significantly improved due to the introduction on Mo, which hindered the carbon deposition due to higher graphitization and abundant active sites accessible to fuel. The detailed Raman spectroscopy and conductivity analysis revealed that addition of Mo reduced the amount of deposited carbon and enhanced the electrical conductivity. By using natural gas, as a fuel, the as-prepared Mo-doped Ni–GDC rendered a maximum power density of 690 mW cm −2 at 600 °C. It is worth mentioning that the achieved stable power density is one of the best in existing literature. The current study presents a novel strategy to improve the catalytic behavior of electrode materials and demonstrate the optimal performance at low operating temperature.